Hubungan Kualitas Pelayanan ANC dengan Perilaku Ibu Hamil dalam Mencegah Terjadinya BBLR - Br Sipayung, Rosmida; Rosmanidar, Rosmanidar; Sabnaniah, Sabnaniah (Universitas Pahlawan Tuanku Tambusai, 2024)
In general, this research aims to determine the relationship between the quality of ANC services and the behavior of pregnant women in preventing the occurrence of LBW, while specifically this research aims to identify the frequency distribution of the quality of ANC services, identify the frequency distribution of behavior of pregnant women in preventing the occurrence of LBW, identify the relationship between quality of service ANC and Pregnant Women's Behavior in Preventing LBW. This type of research uses descriptive analytical survey research with a cross sectional design, which is data collection at one time/with the same conditions and time to see the relationship between the quality of ANC services and the behavior of pregnant women in preventing the occurrence of LBW. From this research it can be concluded that the majority of ANC service quality is good as many as 35 people (60.3%) and the minority is less as many as 23 people (39.7%), the majority of mothers' behavior in preventing LBW is good as many as 38 people (65.5% ) and less than 20 minorities (34.5%), and there is a relationship between the quality of ANC services and the behavior of pregnant women in preventing the occurrence of LBW.